Aberrant early growth of individual trigeminal sensory and motor axons in a series of mouse genetic models of 22q11.2 deletion syndrome. (8th September 2020) - Motahari, Zahra; Maynard, Thomas M; Popratiloff, Anastas; Moody, Sally A; LaMantia, Anthony-S
Abstract: We identified divergent modes of initial axon growth that prefigure disrupted differentiation of the trigeminal nerve (CN V), a cranial nerve essential for suckling, feeding and swallowing (S/F/S), a key innate behavior compromised in multiple genetic developmental disorders including DiGeorge/22q11.2 Deletion Syndrome (22q11.2 DS). We combined rapid in vivo labeling of single CN V axons in LgDel +/− mouse embryos, a genomically accurate 22q11.2DS model, and 3D imaging to identify and quantify phenotypes that could not be resolved using existing methods. We assessed these phenotypes in three 22q11.2-related genotypes to determine whether individual CN V motor and sensory axons wander, branch and sprout aberrantly in register with altered anterior–posterior hindbrain patterning and gross morphological disruption of CN V seen in LgDel +/− . In the additional 22q11.2-related genotypes: Tbx1 +/−, Ranbp1 −/−, Ranbp1 +/− and LgDel +/− : Raldh2 +/− ; axon phenotypes are seen when hindbrain patterning and CN V gross morphology is altered, but not when it is normal or restored toward WT. This disordered growth of CN V sensory and motor axons, whose appropriate targeting is critical for optimal S/F/S, may be an early, critical determinant of imprecise innervation leading to inefficient oropharyngeal function associated with 22q11.2 deletion from birth onward.